Translingual Practices in Digital Environments: A Five-Year Longitudinal Study of Russian-Speaking Ethnic Korean Community - Jang, Jinsil; Yi, Youngjoo (Forum for Linguistic Studies, 2024)
This five-year longitudinal study examines Russian-speaking ethnic Korean community members’ translingual practices in digital environments drawing upon the concept of translingualism. This study aims to investigate the pivotal role of the migrants’ online translingual practices in their daily lives and social integration in South Korea. For this study, data was collected from multiple sources and inductively analyzed. The findings reveal that during the initial settlement in South Korea, Russian-speaking ethnic Korean migrants (called Koryoin) predominantly used the Russian language in online (and offline) interactions as their local practices were mainly centered within the Koryoin community. However, as the migrants immersed themselves into various communities, they had slowly more engaged in translingual practices by switching between and mixing languages (Russian and Korean) for meaningful digital communication. Their translingual practices in digital environments enabled individuals to (1) situate and access resources within a broader online spatial context, (2) (re)build social relationships with other local community members, and (3) challenge social inequality in a host country (Korea). This study underscores the transformative potential of digital translingual practices, which appear to facilitate the (re)allocation of social status within their community and the (re)shaping of their language use. These findings suggest valuable implications for research and pedagogy for marginalized communities around the world.